Evaluation of the Efficacy of Lactobacillus acidophilus in the Treatment of Cyclophosphamide-induced Hemorrhagic Cystitis in Wistar Rats - Minhos, Liandra Ferreira (2023)
Background: Hemorrhagic cystitis is an inflammatory complication that can be caused by the administration of cyclophosphamide, which is widely used as an antineoplastic agent. In the search for new therapeutic alternatives, probiotics can suppress the inflammatory process and, there-fore, can be used to prevent this disease. Objective: Thus, this study aimed to evaluate the effects of using Lactobacillus acidophilus NCFM in the treatment of cyclophosphamide-induced hemorrhagic cystitis in Wistar rats. Methods: Lactobacillus acidophilus NCFM (2x108 CFU) was used in the treatment of cyclophos-phamide-induced hemorrhagic cystitis (200 mg/kg, intraperitoneal) in 77 female Wistar rats. Rats were distributed into experimental groups (n = 9): control group (GC), zero control group (GCZ), inflammation group (GI), 24-hour acute treatment groups: 24-hour lactobacilli treatment group (GL24H) and mesna group (GM), and 30-day chronic treatment groups: lactobacilli treatment group (GTL) and mesna+lactobacilli group (GM+L). After treatment, animals were euthanized and biological materials were collected for blood count, biochemical analyses, examination of abnormal sedi-ment elements (EAS), and histopathological analysis. Results: GI results showed development of edema, macroscopic alterations, and signs of bleeding in the bladder; in addition, lesions in the urothelium and hemorrhage were also found. GL24H and GM presented intact urothelium, without inflammatory reaction and hematological or biochemical urine alterations. Conclusion: Therefore, this study demonstrated that L. acidophilus presented uroprotective effect against the action of cyclophosphamide in both the short and long term.